Anisotropic upper critical magnetic fields in Rb2Cr3As3 superconductor. (13th September 2017) - Tang, Zhang-Tu; Liu, Yi; Bao, Jin-Ke; Xi, Chuan-Ying; Pi, Li; Cao, Guang-Han
Abstract: Rb2 Cr3 As3 is a structurally one-dimensional superconductor containing Cr3 As3 chains with a superconducting transition temperature of T c = 4.8 K. Here we report the electrical resistance measurements for Rb2 Cr3 As3 single crystals, under magnetic fields up to 29.5 T and at temperatures down to 0.36 K, from which the upper critical fields, H c 2 ( T ), can be obtained in a broad temperature range. For field parallel to the Cr3 As3 chains, H c 2 ∥ ( T ) is paramagnetically limited with an initial slope of μ 0 d H c 2 ∥ /d T | T c = − 16 T K − 1 and a zero-temperature upper critical field of μ 0 H c 2 ∥ ( 0 ) = 17.5 T. For field perpendicular to the Cr3 As3 chains, however, H c 2 ⊥ ( T ) is only limited by orbital pair-breaking effect with μ 0 d H c 2 ⊥ /d T | T c = − 3 T K − 1 . As a consequence, the anisotropy γ H = H c 2 ∥ / H c 2 ⊥ decreases sharply near T c and reverses below 2 K. Remarkably, the low-temperature H c 2 ⊥ ( T ) down to 0.075 T c remains to increase linearly up to over three times the Pauli paramagnetic limit, which strongly suggests dominant spin-triplet superconductivity in Rb2 Cr3 As3 .